Enzymatic generation of peptides flanked by basic amino acids to obtain MS/MS spectra with 2× sequence coverage - Ebhardt, H Alexander (Rapid Commun Mass Spectrom, 2014)
RATIONALE: Tandem mass (MS/MS) spectra generated by collision-induced dissociation (CID) typically lack redundant peptide sequence information in the form of e.g. b- and y-ion series due to frequent use of sequence-specific endopeptidases cleaving C- or N-terminal to Arg or Lys residues. METHODS: Here we introduce arginyl-tRNA protein transferase (ATE, EC 2.3.2.8) for proteomics. ATE recognizes acidic amino acids or oxidized Cys at the N-terminus of a substrate peptide and conjugates an arginine from an aminoacylated tRNA(Arg) onto the N-terminus of the substrate peptide. This enzymatic reaction is carried out under physiological conditions and, in combination with Lys-C/Asp-N double digest, results in arginylated peptides with basic amino acids on both termini. RESULTS: We demonstrate that in vitro arginylation of peptides using yeast arginyl tRNA protein transferase 1 (yATE1) is a robust enzymatic reaction, specific to only modifying N-terminal acidic amino acids. Precursors originating from arginylated peptides generally have an increased protonation state compared with their non-arginylated forms. Furthermore, the product ion spectra of arginylated peptides show near complete 2× fragment ladders within the same MS/MS spectrum using commonly available electrospray ionization peptide fragmentation modes. Unexpectedly, arginylated peptides generate complete y- and c-ion series using electron transfer dissociation (ETD) despite having an internal proline residue. CONCLUSIONS: We introduce a rapid enzymatic method to generate peptides flanked on either terminus by basic amino acids, resulting in a rich, redundant MS/MS fragment pattern. © 2014 The Authors. Rapid Communications in Mass Spectrometry published by John Wiley & Sons Ltd.